From the Point of Sales: Purchase-Related Barriers to Condom Use - Tuley, D.L. (University of Ghana, 2002)
Consistent condom use is one of the best ways of stopping the spread of HIV/AIDS and other sexually transmitted diseases (STDs) throughout Ghana. Unfortunately, barriers exist that keep people from using condoms during sex. These barriers range from cultural and religious barriers to barriers resulting from the undesired or lack of sensation condoms provide. This study looks at perceived barriers to condom use in general, but then takes a closer look at those barriers related to condom purchase. These include ease of purchase, brand availability, product display, and condom cost. One hundred sexually active Ghanaians were surveyed about their perceived barriers and condom buying habits. Six different condom retail shops in Accra were also interviewed and observed for insight as to why Ghanaians may not use a condom simply because they are uneasy about buying them. The findings showed that while retail shop owners are hesitant to provide self-service condoms due to theft risks, Ghanaians would be more likely to use condoms if they were sold out in the open and not behind a counter.
Thesis (Mphil)